Knowledge, attitude, and practice toward non-nutritive sweeteners among the population with reduced sugar intake requirement - Chen, Qiao; Zhang, Yan; Li, Hui (Frontiers in Nutrition, 2024)
To explore the knowledge, attitude, and practice (KAP) toward non-nutritive sweeteners among a population with reduced sugar intake requirements. This cross-sectional study used self-developed questionnaires to collect demographic characteristics and KAP towards non-nutritive sweeteners among respondents with reduced sugar intake requirements, i.e., overweight or obese individuals and patients with pre-diabetes or diabetes. A total of 639 valid questionnaires were collected, and 51.64% of participants were male. The KAP scores were 7.63±3.58 (range: 0-11), 34.28±7.47 (range: 12-60), and 15.48±3.97 (range: 7-35), respectively. Pearson’s correlation analysis showed that knowledge score was positively correlated with attitude (r=0.229, P<0.001) and practice score (r=0.467, P<0.001), while attitude was positively correlated with practice (r=0.312, P<0.001). The structural equation model showed that knowledge was directly and positively associated with attitude (path coefficient=0.48, P<0.001) and practice (path coefficient=0.46, P<0.001). In addition, the attitude was directly and positively associated with practice (path coefficient=0.12, P<0.001). Besides, diabetes was associated with lower knowledge (path coefficient=-0.81, P=0.038) and practice (path coefficient=-0.42, P=0.041). Population with the reduced sugar intake requirement showed poor knowledge, negative attitudes, and suboptimal practices toward non-nutritive sweeteners. To optimize the utilization of non-nutritive sweeteners in accordance with medical prescriptions, especially for individuals with diabetes, tailored educational interventions may be designed for participants with lower KAP.